Hereditary gynecological cancer in the genomic era of medicine - Sullcahuaman Allende, Yasser C. (2018)
Cancer is a genetic disease caused by accumulation of sporadic genetic changes in the tumor tissue, generally after the age of 50. However, 10% to 30% of cases occur before the age of 50, some have a family history of cancer and may have inherited genetic changes that are transmitted from generation to generation and are present since conception. The number of genes identified is more than 80 related to approximately 200 genetic syndromes of predisposition to cancer. The importance of detecting these syndromes in patients and their families is because it allows an accurate diagnosis and prediction of risks and specific controls for each person and family, avoiding illness and death in many cases.